PATTERN OF FEMALE MEDICOLEGAL CASES ATTENDING THE CASUALTY DEPARTMENT OF A TEACHING HOSPITAL - Saeed Akbar Tariq; Altaf Pervez Qasim; Muhammad Naeem (Journal of University Medical & Dental College, 2014)
ABSTRACT BACKGROUND: The most important duty of a doctor is to save the life of patient; however, after providing first aid & resuscitative measures, the Casualty Medical Officer has to carry out exhaustive documentation of medico legal cases especially while examining the female victims of physical trauma, domestic violence, attempts of suicide & sexual assault. OBJECTIVES: To study the pattern of medico legal cases in females with regard to age, marital status, and residential backgrounds; those reported for medico legal examination, during one year study period. To find out the incidence and trends of sexual assault in relation the socio demographic characteristics of the female victims of sexual violence. STUDY DESIGN: Retrospective Study: SETTING & DURATION: This study was conducted from 1st January 2012 to 31st December 2012, in Causality Department of tertiary care Hospital attached with Punjab Medical College, Faisalabad. RESULTS: Out of the total 837 cases, Physical violence was observed in 717 (85.66%) victims, sexual assault in 54 (6.45%) cases, 28 (3.34%) victims received Firearm injuries, and 21 (2.50%) cases were injured due to Road Traffic Accidents. The Injuries due to flame burn contributed for 15 (1.80%) cases and 02 (0.23 %) cases were reported to have miscarriage resulting from violence. Among total 54 cases of sexual assault, 30 (55.55%) belonged to urban settings and 24 (44.45%) were inhabitants of rural areas. Majority 37 (68.51%) of sexual assault victims were unmarried girls as compared to 17 (31.49%) married. The highest number of sexual assault 26 (48.15%) was reported among the victims of age group 10-19 years followed by age group 20-29 years involving 19 (35.19%) cases. The semen was detected in 13 (24.07%) cases, negative reports in 09 (16.67%) cases; whereas the reports of Chemical Examiner were not available in the record / medico legal registers in 32 (59.26%) cases of alleged sexual assault. CONCLUSION: The cases of physical violence were high in number followed by injuries due to firearms & road traffic accidents. Sexual assault was more commonly observed in the young girls in age group of 10-19 years majority of being unmarried belonging to urban areas. Public awareness, proper legislation & strict law enforcement are required to reduce such incidences against females.